Friendship and romance across the U.S. political divide: Hindrance or help for outgroup political attitudes?. Issue 3 (25th January 2021) - Buliga, Elena; MacInnis, Cara C.; Hodson, Gordon; Biamonte, Julia
Abstract: Consistent with the intergroup contact literature, cross‐political relationships (e.g., friendships or romantic relationships between different partisans) may help reduce inter‐political group prejudice. Given that unfavorable attitudes based on the political group membership are particularly heightened at present in the United States, we explored whether having cross‐political friendships (Study 1) or romantic relationships (Study 2) predict more positive interpersonal or intergroup attitudes among American Democrats and Republicans. In Study 1, using a social network measure ( N = 301), where participants reported on their closest friends, cross‐political (versus same‐political) friendship was associated with less positive interpersonal attitudes when this relationship was unsatisfying. Having any (versus no) or more (versus less) cross‐political group friendships was not associated with holding more positive intergroup attitudes. In Study 2, cross‐political romantic relationships were examined ( N = 392). Having a cross‐ (versus same‐) political romantic relationship was associated with relatively less positive attitudes toward the political outgroup via lower empathy when relationship satisfaction was low. Study findings highlight the potential limitations of the beneficial effects of intergroup contact.